Strategi Pelayanan Kesehatan Dalam Peningkatan Kinerja Pegawai Puskesmas - Dewi Agustina; Nurhidayah Nurhidayah; Quen Kholisa Purba (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Background: health services with the aim of increasing awareness, willingness and ability to live healthy for everyone in order to realize the highest degree of public health. The role of health workers in dealing with public health is a form of health worker services aimed at the whole community with an emphasis on high-risk groups.The research objective was to determine the role of employee performance in the effectiveness of the service strategy at the health center, in carrying out the best service strategy.research method: This article was written using the article search method using two databases, namely Google Scholar and PubMedd Health with the keywords health service strategy, puskesmas. Results: The performance of the Public Health service strategy at the Community Health Center can be said to be quite good, which can be reflected in the quality of performance, the ability of employees, the timeliness of completing work, cooperation between employees and employee discipline which has been carried out well even though there are still employees who are less conscientious and less disciplined. Factors supporting employee performance are a conducive atmosphere and cooperation between employees, while factors inhibiting employee performance are lack of technical training and lack of awareness of employees in complying with the provisions of working hours. Conclusion: This research suggests that it can be a source of information for related agencies so that they can improve the quality of national health services that are expected to be in accordance with what is received.